YAM_004: Interview with Ivorian (former) teen-mother(s) about sex education and school pregnancies (Health Discourses as Moral Communication? Linguistic Case Studies from Côte d'Ivoire and Cameroon, 2021)
Interview with Ivorian (former) teen-mother(s) about sex education and school pregnancies.
Keywords: Communication; Ethics; Women; Pregnancy; Reproductive health; Africa; Teenage pregnancy; Abortion; Contraception; Prevention; Applied ethics; Birth Control; Moral Communication; Côte d'Ivoire; Ivory Coast; Adolescent Pregnancy; Morality